ANALYSIS OF MACROECONOMIC VARIABLE CHANGES TO THE RESILIENCE OF ISLAMIC BANKING IN INDONESIA - Moh Yusron Solikin (Universitas Airlangga, 2024)
This research aims to analyze the changes in macroeconomic variables such as economic growth, inflation, exchange rates, and interest rates on the resilience of Islamic banking in Indonesia. Additionally, it seeks to prove that Islamic banks are resistant to economic crisis. This quantitative study used monthly data period series of January 2006 to January 2020 with the Autoregressive Distributed Lag (ARDL) and Markov Switching (MS) methods. ARDL test results indicates that economic growth and exchange rates significantly affect Islamic banking resilience. Economic growth has positively influence, while exchange rates have a negative impact. Conversely, inflation and interest rates do not play any role in affecting Islamic Bank resilience. Through the test, Markov Switching proved that Islamic banking is resistant in the face of an economic crisis that lasts more than a period of crisis than a quiet period.